Turning to Simplest Form

Algebra Level 2

x^2+(x+1)^2+(x+2)^2+(x+3)^2+(x+4)^2+(x+5)^2=a(bx+c)^2+d

Which of these equations is non equal to:

(a+d)-bc

Note: a, d are in Q(rationals) whereas b, c are in Z(integers).

(d-a)-(b-c) All are equal to (a+d)-bc c^b-b^(c-1) b^c-(a+d)-c

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sean Bastian
Apr 28, 2019

Once you turn the polynomial into simplest form, you get (3/2)(2x+5)+(35/2).

(a+d)-bc=(3/2+35/2)-10=19-10=9

b^c-(a+d)-c=2^5-(19)-5=32-19-5=32-24=8

Thus B isn't equal to (a+d)-bc.

2 pending reports

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...